Antineutrophil cytoplasmic autoantibodies and anti-Saccharomyces cerevisiae antibodies in inflammatory bowel diseases - Zeki Mesut Yalın KILIÇ; Bilge TUNÇ; Selime AYAZ; Levent FİLİK and Semra AKTAŞ and Erkan PARLAK and Aysel ÜLKER (Turkish Journal of Gastroenterology, 2019)
-